Guerrilha de pincéis: humor gráfico no jornal O Pasquim como resistência política e cultural à ditadura militar (1969 - 1970) - Vieira, Átila Bezerra Fernandes (2010)
The purpose of this dissertation is to analyze the mood chart in Rio tabloid‟s Pasquim. First, the intention is to tell the story of the first two years of the journal (1969-1970), in its political and cultural resistance to military dictatorship, contextualizing it from the analysis of some of his humorous images. The second proposal is - in a direct relationship with the first - to raise some of the topics covered by the newspaper during this period, starting from the various genres of humor employed by the weekly chart. The Pasquim was one of the main representatives, for over 20 years, of the Alternative Press in Brazil, through its editorial posture of reaction, political, cultural and ideological deployed with the military regime in 1964. Weekly cartoon humor that was in one of their languages the caricature, the Pasquim has made during this period of two decades, a critical political ally to another, cultural, which is devoted to call criticism of customs, within the context of the exception regime hardened in 1968.